2020
DOI: 10.1080/15592324.2020.1797294
|View full text |Cite
|
Sign up to set email alerts
|

Mining sequences with similarity to XTH genes in the Solanum tuberosum L. transcriptome: introductory step for identifying homologous XTH genes

Abstract: The xyloglucan endotransglucosylase/hydrolase (XTH) genes in Arabidopsis thaliana (L.) Heynh. form part of a group of mechano-stimulated genes and play an important role in abiotic stress tolerance. Mining the RNAseq transcriptomic database of 40,430 potato (Solanum tuberosum L.) genes based on functional annotation and homology search, our objective was to discover potentially homologous XTH genes. A Gene Ontology-based XTH homology search and functional annotation discovered, from among the 33 A. thaliana (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…(2022) used morphological, biochemical, and molecular markers from Withania somnifera to assess the 25 accessions of Indian ginseng, and concluded that these markers could be used to select superior ginseng genotypes. In addition, XTH genes were also reported to be involved in other abiotic stress, such as salt, heat and cold stress ( Han et al., 2017 ; Hidvégi et al., 2020 ; De Caroli et al., 2021 ). Hence, we suggest that LcXTH genes play roles in drought resistance and other abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) used morphological, biochemical, and molecular markers from Withania somnifera to assess the 25 accessions of Indian ginseng, and concluded that these markers could be used to select superior ginseng genotypes. In addition, XTH genes were also reported to be involved in other abiotic stress, such as salt, heat and cold stress ( Han et al., 2017 ; Hidvégi et al., 2020 ; De Caroli et al., 2021 ). Hence, we suggest that LcXTH genes play roles in drought resistance and other abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that there was a good correlation between the activity of XET and the growth rate and the elongation of cell wall [ 15 , 52 54 ]. Vissenberg et al (2005) reported that the activity of XET was high near the starting point of root hair, and it was believed that XET activity was all high in elongation region of roots in various vascular plants [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies have reported downregulated expression of At XTH15 in Arabidopsis plants with rosette leaves manually folded for 30 minutes [43], suggesting that At XTH15 is a molecule whose expression is downregulated not only under drought but also under stresses such as mechanical stresses. On the other hand, it has been reported that the expression level of At XTH15 increases upon ultrasonic (US) treatment [44], and thus, it is necessary to investigate the relationship with various stress response mechanisms.…”
Section: Xyloglucan Endotransglucosylase/hydrolase (Xth) Familymentioning
confidence: 99%